Bioremediation of Disposed Engine Oil for Lipase Production - Mahmood, Mahmood H.; Zhi, Yang; Thanoon, Raid D.; Makky, Essam A.; Mohd Hasbi, Ab. Rahim (Universiti Malaysia Pahang, 2017)
Engine oil is one of the several refined products of crude oil. It is composed of long chain saturated hydrocarbons (base oil) additives. Generally, engine oil can enter into the environment through leak of oil tankers, cleaning of tanks by merchants, warship carrying engine oil, and operations by motor mechanics which is a common industrial waste that is harmful to environment and human health. This research aims to produce lipase enzyme using microbial degradation of disposed engine oil. In this study hydrocarbon-degrading bacterium, GS-3 was successfully isolated from oil contaminated area. GC-MS analysis revealed that this isolate was able to produce organic acid, methyl-3,4,5-trimethoxy-2,6-dinitrobenzoate from disposed engine oil. Besides, GS-3 isolate produced highest lipase activity, achieving 0.097±0.007 Uml-1min-1 during first 24 hrs when disposed engine oil (DEO) was used as carbon source. Data revealed new and broad band which is related to O-H stretching formed at 3421 cm-1, though new band occurred at 3424 cm-1 and 1645 cm-1 after bioremediation. Subsequent lipase optimization parameters revealed that this bacterial isolate could produce highest lipase activity when the 4% (v/v) DEO was used as carbon source. The best nitrogen source was urea. Addition of surfactant Tween 80 could also enhanced lipase production. Optimal pH value and temperature was 7.0 and 30°C respectively.